(untitled) (International Research Journal of Management and Social Sciences, 2021)
From the source, Pakistan and Iran have been experiencing adequate relations on a large scale due to new priorities and changes in issues that authorize both neighbours to see a few challenges. This paper will explore whether Pakistan and Iran will really need to build a very close relationship in the near future. Regardless, Pakistan has successfully resolved its basic relations with Iran's common enemy Saudi Arabia. On the other hand after 9/11, Iran has been trying to build closer ties with Pakistan's permanent enemy in India. For how long, the article will affect Pakistan's relations with Iran. In addition the paper will include the necessary relations with Iran and Russia and China and it is common for that to continue that will prevent Iran from moving towards India. https://doi.org/10.5281/zenodo.10316609